2021
DOI: 10.1115/1.4052616
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of windthermal turbines: A systematic scoping review of direct wind-to-heat conversion technologies

Abstract: Windthermal turbines convert wind directly into thermal energy. Albeit it is an uncharted field of research, the overall system efficiency and costs of fully developed windthermal turbines are promising; since they can contribute to a sustainable energy transition. We identify the current state of the art of windthermal conversion principles, technology maturity, applications, substitutes, advantages and disadvantages. To scope relevant literature, we follow the Joanna Briggs Institutes selection and screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…The manual for the design and selection of mixing equipment points out that the power of the agitator can be calculated by an empirical formula shown as Formula (9).…”
Section: 𝑃 = 𝑁𝑝 • 𝜌 • 𝑛 • 𝑑mentioning
confidence: 99%
See 1 more Smart Citation
“…The manual for the design and selection of mixing equipment points out that the power of the agitator can be calculated by an empirical formula shown as Formula (9).…”
Section: 𝑃 = 𝑁𝑝 • 𝜌 • 𝑛 • 𝑑mentioning
confidence: 99%
“…However, the heating system requires higher wind speed and quality based on this principle and can only work normally within the rated speed range of the compressor; the system itself is relatively complex and the scope of application is limited as a result. The direct heating mode of wind energy with simple principles and device structure also includes compression heating, friction heating, and induction-based wind heating devices [9]. Zdankus T et al [10] proposed a wind heating device based on a hydraulic system and the heat is produced mainly due to friction losses of this system; the system may reach an overall efficiency of 58.8% under optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Neumeier studied different ways of generating heat based on the wind thermal systems and suggested that the PMECH in wind energy storage systems can achieve temperatures up to 560°C or 600°C. 17 Karasu provided a thermodynamic assessment of a wind thermal energy storage system based on the PMECH system incorporated into the nacelle of the wind turbines for heating the molten salt. He showed that the PMECH system is a cost-effective method for converting wind energy into heat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While several studies have examined the effects of eddy currents on the power loss of electro‐motors, generators, and induction heating devices, few have investigated ways to capture the thermal energy created by eddy currents in renewable energy systems for heating buildings 14–16 . Neumeier studied different ways of generating heat based on the wind thermal systems and suggested that the PMECH in wind energy storage systems can achieve temperatures up to 560°C or 600°C 17 . Karasu provided a thermodynamic assessment of a wind thermal energy storage system based on the PMECH system incorporated into the nacelle of the wind turbines for heating the molten salt.…”
Section: Introductionmentioning
confidence: 99%